Analisis Dan Perancangan Sistem Informasi Layanan Publik Berbasis Web Pada Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Tanjung Jabung Barat - Fajerin, Tommy; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2020)
The system of population document and civil registration services in Tanjung Jabung Barat Regency which is still done manually, as well as the distance to the distant district capitals makes the community must pay a significant amount of cost and time for document management. In this study, an analysis and design of web-based public service information systems at the Department of Population and Civil Registration of West Tanjung Jabung Regency, using the Unified Modeling Language (UML) method as structured modeling in the form of Use Case Diagrams, Class Diagrams, and Activity Diagrams to illustrate the analysis and system design. This research resulted in a design and prototype of a web-based public service information system for submitting applications for Resident Identity Cards, Family Cards, Birth Certificates and Death Certificates. For more complete features, researchers can then add more request types for other documents such as moving certificate, marriage certificate, certificate of endorsement of children, and other deeds of civil registration.